Experimental Investigation on Volume Fraction of Mechanical and Physical Properties of Flax and Bamboo Fibers Reinforced Hybrid Epoxy Composites. Issue 3 (March 2017) - Sathish, S.; Kumaresan, K.; Prabhu, L.; Vigneshkumar, N.
The aim of this paper is to study the effect of volume fraction on mechanical and physical properties such as tensile, flexural, impact, interlaminar shear strength, void content and water absorption of flax and bamboo fibers reinforced hybrid epoxy composites. Flax and bamboo fibers reinforced epoxy resin matrix hybrid composites have been fabricated by compression molding techniques. The hybrid composites were fabricated with different volume fraction of fibers. SEM analysis on the hybrid composite materials was performed to analyze the bonding behavior of materials and internal structure of the fractured surfaces. The effect of chemical treatment of flax and bamboo fibers was verified by FTIR analysis. The results showed that the tensile, impact, flexural and ILSS are maximum for 40:0 (flax: bamboo) hybrid composites. The void content decreased for 20:20 (flax:bamboo) composites due to tightly packed flax fiber and more compatibility towards epoxy resin.